THE EVALUATION OF ANTIMICROBIAL AND CYTOTOXIC ACTIVITY OF THE ESSENTIAL OIL EXTRACTED FROM THE AERIAL PARTS OF SOUTHERNWOOD HERB (ARTEMISIA ABROTANUM L.) THAT RECENTLY GROWN IN IRAQ - Almahdawy, Sarah S; Said, Ali Muaffaq; Abbas, Ibrahim S; Dawood, Ashour H (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: This research is to study the assessment of the antimicrobial and cytotoxic activity of the essential oil extracted from the aerial parts of Artemisia abrotanum L. that recently grown in Iraq. Methods: The essential oil of A. abrotanum was extracted by hydrodistillation using Clevenger apparatus. This essential oil was tested for antimicrobial activity of five different pathogenic microorganisms (Gram-positive [Staphylococcus aureus and Bacillus subtilis] and Gram-negative [Salmonella typhi and Escherichia coli] bacterial strains) and fungi: Candida albicans using diffusion well agar method. Furthermore, this essential oil was tested for cytotoxic activity using rhabdomyosarcoma cell line, and the growth or inhibition of cancer cells was measured by MTT method. Results: The obtained results show that the antibacterial activity for A. abrotanum against S. aureus was at concentrations 40, 25, and15 Î¼l with minimum inhibitory concentrations of 20 mm, while it showed antibacterial activity against E. coli for four different concentrations of 40, 25, 15, and10 Î¼l with inhibition zone of 16, 12, 14, and 10 mm, respectively, and it showed antifungal activity against C. albicans at four concentrations 40, 25, 15, and10 Î¼l with inhibition zone of 18, 24, 26, and 30 mm, respectively. The cytotoxic activity of the extracted essential oil was showed that the three concentrations of the extract (25, 50, and 100 Î¼g/ml) were all lower significantly as compared to dimethyl sulfoxide group. A significant difference was seen for group 25 with both groups 50 and 100, but no significant difference was seen between the two later. Finally, the antimicrobial and anticancer activity of this plant could be due to its essential oil constituents: Borneol, cymene, camphor, terpineol, eucalyptol, and aromadendrene. Conclusion: The essential oil of A. abrotanum L. has a potent antimicrobial and anticancer effect against the tested microbial organisms and the cancer cells.